Early Childhood Learning Model in the Perspective of Islamic Education: Efforts to Grow Children's Fitrah and Morals - Maygischa Putri Adzuhra; Akmelia Maulida; Nazwa Mailan Nanda Arif; Rindu Aprelia; Lathipah Hasanah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to examine the variety of learning models used in Early Childhood Education (PAUD) and their implementation in supporting children's holistic development. From the perspective of Islamic education, learning in PAUD is not only understood as a pedagogical strategy, but also as part of the process of ta'lim, ta'dib, and tazkiyah which is oriented towards the maintenance of fitrah, the cultivation of adab, and the formation of faith and noble morals from an early age. The method used is literature research by examining various relevant scientific literature related to the PAUD learning model. The results of the study showed that the area model, center, group learning with safety activities, and classical corners each have advantages in stimulating children's cognitive, social, emotional, and motor development through an active and fun learning experience. More than that, the application of these models has the potential to be a means of fostering spiritual values such as compassion, responsibility, discipline, and awareness of God's existence in children's daily activities. Learning in PAUD is thus an effort to maintain the nature of children so that they remain holy, grow with curiosity, and develop as individuals who have faith, morals, and are ready to live a balanced life.